Sikap Orang Percaya dalam Menghadapi Kesukaran: Refleksi Surat-surat Petrus - Molina, Soleman Daud (Sekolah Tinggi Teologi Berita Hidup, 2021)
The background of this paper is the hardships of life that humans experience universally. Life difficulties are facts of human life that cannot be avoided in human life, one of which is the Covid-19 pandemic that has hit the world. In particular, this paper discusses the hardships of life experienced by believers in the letter of Peter. The problematic issue of this problem is the hardships of life experienced by followers of Christ who experienced cruel persecution in the mass of Nero's reign. Whether the hardships of life experienced by believers become a force of faith, or do they leave their faith in Christ because of the suffering they have experienced. To answer this problem the researcher used the literature method with a descriptive qualitative approach, the researcher also conducted studies from several sources in the form of theological journals, theology books related to the theme and used the Bible as the primary source. From the research results, the researcher found the answer that the difficulties of living according to Peter's theology are life difficulties experienced by the Lord's congregation which can prove the purity of their faith, the hardships or sufferings experienced because Christ is the grace of God, the suffering of Christ is an example that must be imitated and follow in his footsteps. suffering for Christ is a joyPenulisan paper ini dilatarbelakangi dengan adanya kesukaran hidup yang dialami manusia secara universal. Kesukaran hidup merupakan fakta-fakta kehidupan manusia yang tidak dapat dihindari dalam kehidupan manusia salah satunya adanya pandemi Covid-19 yang melanda dunia. Secara khusus paper ini membahas kesukaran hidup yang dialami orang percaya dalam surat Petrus, pokok problematis permasalahan ini adalah adanya kesukaran hidup yang dialami oleh pengikut Kristus yang mengalami penganiayaan yang kejam pada massa pemerintahan Nero. Apakah kesukaran hidup yang dialami orang percaya menjadi kekuatan iman, atau sebaliknya mereka meninggalkan iman percaya mereka kepada Kristus karena penderitaan yang mereka alami. Untuk menjawab permasalahan ini peneliti menggunakan metode pustaka dengan pendekatan kualitatif deskriptif, peneliti juga melakukakan kajian dari beberapa sumber berupa jurnal teologi, buku-buku teologi yang berhubungan dengan tema dan menggunakan Alkitab sebagai sumber primer. Dari hasil penelitian, peneliti menemukan jawaban bahwa kesukaran hidup menurut teologi Petrus merupakanÂ kesukaran hidup yang dialami jemaat Tuhan dapat membuktikan kemurnian iman mereka, kesukaran atau penderitaan yang dialami karena Kristus adalah kasih karunia Allah, penderitaan Kristus adalah sebuah teladan yang harus dicontoh dan mengikuti jejaknya, menderita bagi Kristus adalah suatu kebahagiaan.